Needs Analysis for Developing EFL Academic Writing Materials: Lecturer Perspectives - Tustiawati, Ida Ayu Mela; Putra, I Gde Agoes Caskara Surya; Hikmaharyanti, Putu Desi Anggerina (Langkawi: Journal of The Association for Arabic and English, 2024)
This study is one part of a larger study that aims to develop instructional material in the form of a handbook for second-year university students who take an academic writing unit. A qualitative method was employed as the design of this study, involving an in-depth exploration of the lecturer's perspectives and practices. We purposefully recruited four lecturers who taught this unit as study participants to gain authentic perspectives of the intended study context. The data were collected using semi-structured interviews with ten prepared open-ended questions as a guideline and additional questions as needed. Any recurring topics and patterns from the collected data were further identified using a framework developed by Braun and Clarke (2006). The findings categorized issues faced by EFL students in academic writing into three themes: 1) language skills, 2) writing skills, and 3) technology integration. These challenges focus on grammatical structures, paragraph and essay construction, awareness of plagiarism, and proper use of technology to support their writing practice. Meanwhile, in terms of instructional material development, as well as the three factors above, the study revealed the need to include four relevant teaching activities in the process. Therefore, the suggested topics for the instructional materials centre around these four categories.